2014
DOI: 10.1016/j.jpubeco.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the nature of cooperation variability

Abstract: We investigate framing effects in a large-scale public good experiment. We measure indicators of explanations previously proposed in the literature, which when combined with the large sample, enable us to estimate a structural model of framing effects. The model captures potential causal effects and the behavioral heterogeneity of cooperation variability. We find that framing only has a small effect on the average level of cooperation but a substantial effect on behavioral heterogeneity and we show that this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 34 publications
7
45
2
Order By: Relevance
“…14 As such, the potential malleability of types might constitute a challenge when trying to assess the empirical relevance of certain behavioral theories (e.g., pure outcome-oriented models), since such tests usually need to rely on a selection of data from different kinds of games. Given the importance of such assessments, we believe that one should try to learn more about why (or which) people react to differences in framing, so that these relevant factors could be controlled for (e.g., see Fosgaard et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…14 As such, the potential malleability of types might constitute a challenge when trying to assess the empirical relevance of certain behavioral theories (e.g., pure outcome-oriented models), since such tests usually need to rely on a selection of data from different kinds of games. Given the importance of such assessments, we believe that one should try to learn more about why (or which) people react to differences in framing, so that these relevant factors could be controlled for (e.g., see Fosgaard et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Allison and Messick, 1985;Dufwenberg et al, 2011;Khadjavi and Lange, forthcoming), while others find little difference (e.g. Fleishman, 1988;Cubitt et al, 2011;Cox et al, 2013;Stoddard, 2014;Fosgaard et al, forthcoming). Some studies find the opposite (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Gächter, Kölle, and Quercia (2017) [11] found that framing the public good game as a Maintenance or a Provision problem affects the elicited contribution profiles. 5 Different kinds of framing effects have been shown to affect contributions in public good games (e.g., Andreoni 1995 [14]; Ellingsen et al, 2012 [15]; Dufwenberg et al 2011 [16]; Fosgaard, Hansen,Wengström, 2014 [17]; Nikiforakis, 2010 [18]). For an extensive list of references, see Cartwright (2016) [19].…”
Section: The Experimentsmentioning
confidence: 99%